Identifiy student’s attitude towards the subject of natural science - Astalini Astalini; Dwi Agus Kurniawan; Darmaji Darmaji; Aqina Deswana Putri; Retno Nawangsih (Intelektual Pustaka Media Utama, 2019)
The purpose of this research is to know how the attitude of junior high school students to science mathematics with three indicators adopted from TOSRA are: 1) pleasure in learning science, 2) interest to increase study time of science, and 3) interest in a career in the science field. This research uses survey type research with design research is quantitative design. This research was conducted in several junior high schools in Muaro Jambi district with total 2815 of total students. The instruments used are attitude questionnaires and interview sheets. The data analysis used for quantitative data is the descriptive statistical type and reinforced by interview analysis. The result of the research shows that students with the indicator of pleasure in learning science, and interest in increasing the study time dominant IPA has a good attitude category, while the indicator of career interest in the field of IPA dominant has a fairly good attitude category.